2015
DOI: 10.1101/029421
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reconstructing Genetic History of Siberian and Northeastern European Populations

Abstract: Siberia and Western Russia are home to over 40 culturally and linguistically diverse indigenous ethnic groups. Yet, genetic variation of peoples from this region is largely uncharacterized. We present whole-genome sequencing data from 28 individuals belonging to 14 distinct indigenous populations from that region. We combine these datasets with additional 32 modern-day and 15 ancient human genomes to build and compare autosomal, Y-DNA and mtDNA trees. Our results provide new links between modern and ancient in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…However, we caution that this pends further verification via more GWAS on the same trait. Our modeling framework suggests that, if selection truly operated on these variants, it must have done so before or early in the process of divergence among East Asian populations -at least as far back as 5 thousand years ago (Stoneking and Delfin 2010;Fu et al 2013;Wong et al 2017;Lu et al 2016) -because the signal is common to different East Asian populations (Han Chinese, Dai Chinese, Japanese, Koreans, etc.). The signal seems only very weakly present in some Siberian populations -like the Even and Nganasan -and some Native American populations -like the Mixe and Pima, and not present at all in other Native American populations -like the Surui, Quechua and Karitiana.…”
Section: Discussionmentioning
confidence: 99%
“…However, we caution that this pends further verification via more GWAS on the same trait. Our modeling framework suggests that, if selection truly operated on these variants, it must have done so before or early in the process of divergence among East Asian populations -at least as far back as 5 thousand years ago (Stoneking and Delfin 2010;Fu et al 2013;Wong et al 2017;Lu et al 2016) -because the signal is common to different East Asian populations (Han Chinese, Dai Chinese, Japanese, Koreans, etc.). The signal seems only very weakly present in some Siberian populations -like the Even and Nganasan -and some Native American populations -like the Mixe and Pima, and not present at all in other Native American populations -like the Surui, Quechua and Karitiana.…”
Section: Discussionmentioning
confidence: 99%
“…TreeMix jointly estimates population splits and subsequent admixture events based on the Fstatistics introduced by Reich et al (2009), and commonly recognised as a valid support for admixture (e.g., in humans: Pickrell & Pritchard 2012, Wong et al 2017. A maximum-likelihood population tree was estimated based on the matrix of GBS allele frequency covariance between population pairs, and admixture events were sequentially added.…”
Section: Analyses Of Admixture In the Mytilus Sppmentioning
confidence: 99%
“…Kerguelen population was performed with TreeMix v.1.1(Pickrell & Pritchard 2012).TreeMix jointly estimates population splits and subsequent admixture events based on the Fstatistics introduced by Reich et al(2009), and commonly recognised as a valid support for admixture (e.g., in humans:Pickrell & Pritchard 2012, Wong et al 2017. A maximum-likelihood…”
mentioning
confidence: 99%
“…The same inference can be drawn from phylogenetic data, as only two Mansi samples appeared in our phylogenetic trees on the side branches (S1 Figure, Networks 1, 4) suggesting that ancestors of the Mansis separated from Asian ancestors of the Conquerors a long time ago. This inference is also supported by genomic Admixture analysis of Siberian and Northeastern European populations [90], which revealed that Mansis have very ancient North Eurasian ancestry, who in addition received a significant (43%) Eastern Siberian genetic component approximately 5-7 thousand years ago from ancestors of modern Even and Evenki people. Most likely the same explanation applies to the Y-chromosome N-Tat marker which originated from China [91], [92] and its subclades are widespread between various language groups of North Asia and Eastern Europe [93].…”
Section: Finno-ugric Relationsmentioning
confidence: 75%